Tinjauan Analisis Panel dan Appellate Body WTO Pada Sengketa Hambatan Teknis Dalam Perdagangan - Panjaitan, Anggia Rettrisunz P I M (Faculty of Law, Universitas Airlangga, 2023)
Abstract One of the WTO disputes that have recently been rife are disputes over technical barriers. Within the WTO itself, arrangements related to technical barriers are contained in the Agreement on Technical Barriers to Trade (TBT Agreement). Generally, disputes over technical barriers are associated with violations of the provisions of Articles 2.1 and 2.2 of the TBT. However, what constitutes a violation of the non-discrimination principle in Article 2.1 of the TBT? And what is the basis for the violation of the provisions of Article 2.2 TBT? This article will attempt to explore the elements of violations in Articles 2.1 and 2.2 of the TBT. The analysis will refer to previous disputes such as the DS381 (US-Tuna II Case), DS384 (US-COOL Case), and DS406 (US-Clove Cigarette Case). These disputes contain various landmark decisions that produce new precedents which are then later to be used as a reference on future technical barriers dispute. This article attempts to describe the interpretation and analysis of the panel and the appellate body in analyzing the elements of violations of the provisions of Articles 2.1 and 2.2 of the TBT. Keywords: Technical Barriers, Non-Discrimination, Unnecessary trade restrictive barriers Abstrak Salah satu sengketa WTO yang akhir-akhir ini marak terjadi adalah sengketa hambatan teknis. Dalam WTO itu sendiri, pengaturan terkait dengan hambatan teknis termuat dalam Agreement on Technical Barriers to Trade (Perjanjian TBT). Umumnya, sengketa hambatan teknis dikaitkan dengan pelanggaran terhadap ketentuan Pasal 2.1 dan 2.2 TBT. Namun demikian, apa yang disebut sebagai pelanggaran terhadap prinsip non-diskriminasi dalam Pasal 2.1 TBT? Dan apa yang menjadi dasar adanya pelanggaran terhadap ketentuan Pasal 2.2 TBT? Artikel ini akan berupaya mengupas unsur-unsur pelanggaran dalam Pasal 2.1 dan 2.2 TBT. Analisa tersebut akan mengacu pada sengketa terdahulu seperti DS381 (US-Tuna II Case), DS384 (US-COOL Case), dan DS406 (US-Clove Cigarette Case). Ketiga sengketa tersebut memuat berbagai landmark decision yang menghasilkan preseden-preseden baru yang kemudian dimanfaatkan sebagai rujukan pada sengketa hambatan teknis selanjutnya. Artikel ini berupaya untuk menjabarkan penafsiran dan analisa panel maupun appellate body dalam menganalisa unsur pelanggaran terhadap ketentuan Pasal 2.1 dan 2.2 TBT. Kata Kunci: Hambatan Teknis, Non-Diskriminasi, Hambatan perdagangan yang tidak diperlukan